Analysis of heavy truck maintenance issues - Škerlič, Sebastjan (Array, 2020)
The objective of the study is to determine whether the scientific literature in the field of heavy truck maintenance parallels current development trends in maintenance. For this purpose, models related to fleet maintenance were analysed in terms of cost optimization, decision-making support and improving employees’ maintenance competencies. The analysis underlines the lack of research in the studied field and highlights the scientific gap in the development of methodological approaches to improving the competencies of truck drivers as important entities in the process of detection and elimination of technical issues. The analysis of heavy truck maintenance issues therefore serves as empirical support for the improvement of maintenance processes in the addressed industry as well as in logistics in general. The resulting research also synthesizes the scientific literature in the field of fleet maintenance, which represents an important support for future empirical studies.